THE MAINTENANCE OF MINANGKABAUNESE FOUND IN SUNGAI LANDIA - Nessa Harliyani; Fitrawati Fitrawati (English Language and Literature, 2016)
The purpose of this article is to know the words that still maintained in Sungai Landia and the factors that those words still exist. The data were collected through interview from 10 informants. Based on findings, there are 111 words that still maintained in Sungai Landia. It consists of 34 nouns, 27 adjectives, 34 verbs, 8 adverb (times), 5 adverb (degrees), and 3 directionals. The factors that those words still maintained, such language loyalty and pride of language itself, globalization, customs, population and location, the concern for the language. Based on findings and discussion, Sungai Landia’s people should increase language maintenance so that language shift or language death will never happen.